Correlation of Serum Ferritin with Child-Pugh and MELD Scores in Decompensated Liver Cirrhosis (Bangladesh Medical Journal, 2026)
Decompensated cirrhosis is associated with substantial morbidity and mortality. The Child-Turcotte-Pugh (CTP) and Model for End-Stage Liver Disease (MELD) scores are established tools for severity assessment, but inexpensive adjunctive biomarkers may be useful in resource-limited settings. Serum ferritin, an iron-storage protein and acute-phase reactant, may reflect inflammation, hepatocellular injury, and worsening liver disease.Materials and Methods: This cross-sectional study was conducted at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from April 2021 to March 2022. A total of 33 patients with decompensated liver cirrhosis were enrolled consecutively. Patients were categorized by ferritin level (400 ng/mL). Correlation was assessed using Spearman’s rank test. Multivariable analyses were performed using binary logistic regression for high MELD score (>15) and multiple linear regression for continuous MELD score, adjusting for age, sex, serum bilirubin, and serum albumin. A p-value